Pengenalan Akan Allah Menurut Hosea 6:6 dan Relevansinya Dimasa Kini Bagi Orang Percaya - Welong, Gabriela Avril (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2023)
The purpose of this research is to emphasize the knowledge of God as articulated in Hosea 6:6. This verse serves as a key to understanding the relationship between God and His people, highlighting that knowing Him is far more valuable than religious rituals often performed without awareness or sincerity. According to Tjatur Raharso Yustinus et al. in